Fragment Screening of Human Aquaporin 1 - To, Janet (2016)
Aquaporins (AQPs) are membrane proteins that enable water transport across cellular plasma membranes in response to osmotic gradients. Phenotypic analyses have revealed important physiological roles for AQPs, and the potential for AQP water channel modulators in various disease states has been proposed. For example, AQP1 is overexpressed in tumor microvessels, and this correlates with higher metastatic potential and aggressiveness of the malignancy. Chemical modulators would help in identifying the precise contribution of water channel activity in these disease states. These inhibitors would also be important therapeutically, e.g., in anti-cancer treatment. This perceived importance contrasts with the lack of success of high-throughput screens (HTS) to identify effective and specific inhibitors of aquaporins. In this paper, we have screened a library of 1500 “fragments”, i.e., smaller than molecules used in HTS, against human aquaporin (hAQP1) using a thermal shift assay and surface plasmon resonance. Although these fragments may not inhibit their protein target, they bound to and stabilized hAQP1 (sub mM binding affinities (KD), with an temperature of aggregation shift ΔTagg of +4 to +50 °C) in a concentration-dependent fashion. Chemically expanded versions of these fragments should follow the determination of their binding site on the aquaporin surface.